PENGARUH FIRM SIZE DAN GROWTH OPPORTUNITY TERHADAP FIRM VALUE MELALUI CASH HOLDING SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Damayanti, Dini Aura; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
At this time the company is no longer focused on seeking profit and prioritizing profits and assets in growing the company but on valuation. Changes in technology have made small companies global. Companies big or small can no longer be separated. The purpose of this study was to analyze and examine the effect of Firm size and Growth opportunity on Firm value through Cash holding as an intervening variable in the Property and Real Estate sub-sector companies on the IDX. The population in this study are all property and real estate companies that have gone public on the Indonesia Stock Exchange for the 2016-2020 period as many as 80 companies. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM).The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Firm size has a positive but not significant effect on Cash holding, Growth opportunity has a positive significant effect on Cash holding, Firm size has a negative but not significant effect on Firm value, Growth opportunity has a positive but not significant effect significant effect on Firm value, Cash holding has a significant positive effect on Firm value. The results of the indirect effect hypothesis test show that the Firm size variable has a positive but not significant effect on Firm value through Cash holding, Growth opportunity has a significant positive effect on Firm value through Cash holding.